A descriptive analysis of patient’s preferences in bone graft therapy in dentistry - Almutairi, Abdullah S. (International Journal of Health Sciences, 2019)
Objectives: Therapeutic and procedural aspects have been primarily focused on the bone graft treatments with least priority to patients’ perception and preferences. Therefore, the aim of this study was to assess the patient’s choices about various bone grafts used in the bone replacement dental treatments. Methods: A self-structured, an anonymous questionnaire with eight items was administered to 100 patients. The questionnaire recorded the responses of selected patients regarding their acceptance and refusal to each type of bone grafts; intraoral and extraoral autograft, allograft, xenograft, and alloplast. The patients’ responses were compared with age, gender, and educational level. The descriptive statistical analysis was performed for the collected data, and with P < 0.05 was considered statistically significant. Results: The overall acceptance ratio for intraoral autografts, extraoral autografts, allografts, xenografts, and alloplasts was 89%, 72%, 46%, 33%, and 87%, respectively. The xenograft (67%) had the highest rate of refusal followed by allografts (54%), extraoral autogenous grafts (28%), alloplast (13%), and intraoral autograft (11%) being the least refused bone graft. Age had no statistically significant influence on the acceptance rate to different types of bone grafts, whereas the gender and educational levels were associated with higher acceptance rates. Conclusions: The xenograft (67%) had the highest rate of refusal, followed by allografts (54%), extraoral autogenous grafts (28%), alloplast (13%), and intraoral autograft (11%) being the least refused bone graft among the surveyed participants. Moreover, age had no statistically significant influence on the acceptance and refusal to different types of bone grafts, whereas the gender and education level was associated with the acceptance and rejection rates.